The Effect of the Electoral System on Women's Elections in Parliament (Case Study of South Korea) - Hilda Indah Bahirah (Universitas Muhammadiyah Malang, 2023)
This paper aims to examine the effect of the general election system on women's electability in the South Korean parliament. South Korea, which is known as a great economic and human development country, in fact, when it comes to issues of gender equality is not comparable to the greatness of the country. In this context, South Korea received the title as one of the countries with a high gender gap. The research method used in this paper is qualitative-descriptive. The results of this study indicate that the gap between women and men in South Korea is still high so that the number of women involved in parliament is still very limited. In addition, there are still several inhibiting factors when women want to become members of parliament. Whereas the presence of women in Parliament is a very important thing because they are considered to be able to bring ideas and ideas that can represent the interests of their constituents. The presence of a proportional representation system does indeed seem to provide a positive enough opportunity to increase the representation of women in the South Korean Parliament through a 30% quota which is believed to be sufficient to provide good things for effective and efficient elections in legislative elections. Even though this proportional representation system is not fully capable of bringing about such significant changes in results, at least the existence of this system is enough to help women improve their representation, or it can be said that slowly, but the results are enough to bring bigger changes to women's representation in parliament.